Development of an implementation intervention to promote adoption of the COMFORT clinical practice guideline for peripartum pain management: a qualitative study - Limi Sharif; Shelytia Cocroft; Shawna N. Smith; Christopher Benincasa; Alex F. Peahl; Lisa Kane Low; Jennifer Waljee; Carrie Miller; Carey Simpson; Michelle H. Moniz (Implementation Science Communications)
Abstract Background Pain management after childbirth is widely variable, increasing risk of untreated pain, opioid harms, and inequitable experiences of care. The Creating Optimal Pain Management FOR Tailoring Care (COMFORT) clinical practice guideline (CPG) seeks to promote evidence-based, equitable acute peripartum pain management in the United States. We aimed to identify contextual conditions (i.e., barriers and facilitators) and discrete implementation strategies (i.e., theory-based actions taken to routinize a clinical practice) likely to influence COMFORT CPG uptake and specify corresponding multi-component implementation interventions at the perinatal quality collaborative- and unit-level. Methods We conducted a qualitative study involving virtual individual interviews and focus groups. Interviews included individuals undergoing childbirth from 2018–2023, (recruited through two online registries), and actively practicing maternity clinicians and surgeons, (recruited via snowball sampling with the eDelphi panel creating the COMFORT CPG), caring for pregnant people in the United States. Focus groups included physicians, midwives, nurses, and unit-based quality improvement (QI) staff working at Michigan hospitals within the Obstetrics Initiative, a statewide perinatal quality collaborative funded by Blue Cross Blue Shield of Michigan and Blue Care Network. The Consolidated Framework for Implementation Research, Expert Recommendations for Implementing Change taxonomy, and Replicating Effective Programs framework informed data collection and analysis. Qualitative content analysis characterized influential contextual conditions, which were linked to implementation strategies and tools using principles of implementation mapping. We then specified multi-component implementation interventions for use by quality collaboratives and unit-based teams. Results From May–September 2023, we completed 57 semi-structured individual interviews (31 patients, 26 clinicians) and six focus groups (44 QI champions). Participants identified 10 key conditions influential for COMFORT CPG adoption. Findings enabled identification of five collaborative-level implementation strategies, 27 unit-level implementation strategies, and 12 associated tools to promote COMFORT CPG adoption including the specification of each strategy’s hypothesized mechanism of action and each tool’s goal and potential uses. Conclusions This work identifies contextual conditions and implementation strategies and tools at the perinatal quality collaborative and unit levels to promote COMFORT CPG adoption on maternity units. These findings may foster more rapid CPG implementation and thereby promote more equitable and evidence-based perinatal pain management care.